التحليل الحراري للمحرّك التحريضي باستخدام النموذج البارامتري المجمّع - حسن, عزت; حسام الدين, علاء الدين (Latakia University Journal -Engineering Sciences Series, 2018)
This paper presents an explanation of one of the analytical methods used in thermal analysis of the induction motor. The thermodynamic analysis was performed on a three phase Totally Enclosed Fan-Cooled (TEFC) induction motor according to the combined parameter method, which assumes that the parameter of whatever object can be studied on one point of this object that represents to the mean parameter point. Then we modified the motor design by adding non-insulated aluminum plates between the windings in the stator slots to improve the heat transfer that is caused by the copper losses in these windings to the internal air. The thermal model has been modified according to the change resulting from this design modification. The thermal equations of the two cases were modeled and compared. The results showed that the addition of plates led to a decrease in the temperature of the stator winding by two degrees, the temperature of the end winding by one and a half of degree, and decreased the temperature of the air gap by one degree Celsius, which is reflected positively on the investment of induction motors and increase the age of isolation . يقدم هذا البحث شرحاً لإحدى الطرق التحليلية المستخدمة في التحليل الحراري للمحرك التحريضي. حيث تم إجراء عملية التحليل الحراري على محرك تحريضي ثلاثي الطور مغلق ومزود بمروحة تبريد وفق طريقة البارامترات المجمعة التي تفترض أن البارامتر أيّاً كان في أي جسم يمكن أن يدرس على نقطة واحدة من هذا الجسم تمثّل نقطة البارامتر المتوسطة. ثم قمنا بتعديل تصميمي على المحرّك بأن أضفنا صفائح غير معزولة من الألمنيوم بين الملفات ضمن مجاري الثابت بهدف تحسين عملية انتقال الحرارة الناتجة عن الضياعات النحاسية في هذه الملفات إلى الهواء الداخلي. تم تعديل النموذج الحراري تبعاً للتغير الحاصل نتيجة هذا التعديل التصميمي، حيث تمت نمذجة المعادلات الحرارية للحالتين وإجراء المقارنة بينهما، حيث أظهرت نتائج النمذجة أن إضافة الصفائح أدت إلى انخفاض في درجة حرارة القسم الفعال للملفات بمقدار درجتين، كما انخفضت درجة حرارة القسم الجبهوي درجة ونصف الدرجة، وانخفضت درجة حرارة الثغرة الهوائية بمقار درجة مئوية واحدة، الأمر الذي ينعكس إيجابياً على استثمار المحرّكات التحريضية وزيادة عمر العازلية.